Sustainability study of u-turn at km16 – km 18, Jalan Kuantan - Gambang - Nor Azliayana, Ahmad Nordin (2017)
In Malaysia, the rapid growth in the automobile industry springing up like mushrooms after the rain. The affordable prices of vehicles resulted in Malaysians race to buy more that made a total of 4.91 million of vehicles have been registered to JPP in 2015. Within the increasing number of vehicles, the capacity of vehicles on the road is also increase. The objectives of this study are to identify the driving behavior during peak hour, to identify causes of traffic congestion at peak hour and to assess the sustainability of U-turn at the Kuantan- Panching intersection, Jalan Kuantan - Gambang. The study area is located at Federal Road 2 from KM16 until KM18 Jalan Kuantan – Gambang. A set of video recorder was used as an observation device in the study area to collect the data on driving behavior and congestion factor within this area. The duration of recording is two hours, respectively, during peak hours from 7 a.m. to 9.a.m , 12.00 p.m. to 2 p.m. , and 4 p.m. to 6 p.m.. The result of this study showed the common driving behavior done by road user’s at the study areas which are red light running, failing to signal, queue jumping, make an illegal U-turn and do not wear the helmet. The result also showed that the factor that lead to congestion happen is the more vehicles queuing in waiting for making a U-turn or right turn to Sg. Pahncing outside the storage lane. This situation happens cause inadequate design of storage length that failing to accommodate the maximum vehicles queuing during peak hour. Results from this study is the hope that the parties concerned, such as the Public Works Department (JKR) or Kuantan Council (MPK) can make some improvements of existing design in order to reduce the traffic congestion and indirectly will provide good benefits to road users in daily travel.